2000
DOI: 10.1302/0301-620x.82b1.0820062
|View full text |Cite
|
Sign up to set email alerts
|

Radical surgery for the solitary bony metastasis from renal-cell carcinoma

Abstract: W e carried out excision of a solitary bony metastasis from renal-cell carcinoma in 25 patients in the hope that this would produce a prolonged disease-free interval. Two patients had excisions only, five had amputations and 18 had excision and endoprosthetic replacement. The one-, three-and five-year cumulative survival rates were 88%, 54% and 13%, respectively.There were three complications. One patient developed a local recurrence and three had problems related to the endoprosthesis.We recommend radical exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 20 publications
1
31
0
1
Order By: Relevance
“…Some authors argue that, for patients with a long projected survival, an endoprosthesis is the more durable surgical option [5,21]. Some have even suggested that EPR should be the treatment of choice in isolated lesions from renal cell metastasis because these patients may have prolonged survival [1,15]. In our series, 51% of patients survived 1 year, 29% survived 2 years, and 11% survived 5 years.…”
Section: Discussionmentioning
confidence: 56%
“…Some authors argue that, for patients with a long projected survival, an endoprosthesis is the more durable surgical option [5,21]. Some have even suggested that EPR should be the treatment of choice in isolated lesions from renal cell metastasis because these patients may have prolonged survival [1,15]. In our series, 51% of patients survived 1 year, 29% survived 2 years, and 11% survived 5 years.…”
Section: Discussionmentioning
confidence: 56%
“…58 In addition to general prognostic factors, peripheral location of bone metastases is a favourable factor. 12,[59][60][61][62] Only two studies were identifi ed that compared diff erent radiotherapy modalities, including in combination with surgery, for brain metastases from renal cell carcinoma. Thus, recommendation of a specifi c treatment modality is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate resection margins are the surgically independent risk factor for local recurrence and patient survival [17,18]. Excision of solitary metastases with adequate margins (and adjuvant therapy) may provide prolonged survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate resection margins are the surgically independent risk factor for local recurrence and patient survival [17,18]. Excision of solitary metastases with adequate margins (and adjuvant therapy) may provide prolonged survival [17]. Excision of metastatic tumours in the presence of multiple metastases may be performed for intractable pain, and for impending or pathological fractures [19].…”
Section: Discussionmentioning
confidence: 99%